Learning Strategies Online and Offline at SD Muhammadiyah 8 during the Covid 19 Pandemic - Imamatut Tarbiyah; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This study aims to analyze learning strategies by teachers during the Covid-19 pandemic. This research was carried out at SD Muhammadiyah 8 Tulangan in the Even semester of the 2020/2021 academic year. This research was conducted using qualitative methods. The subjects in this study were students and also elementary school teachers at SD Muhammadiyah 8 Tulangan who carried out the activities. The data collection instruments in this study were document studies, observation sheets, and guidelines from interviews. The results showed that the strategy for implementing learning during the Covid-19 pandemic included 1) Teachers already had technological devices used in the online learning process through What's App Group media, Zoom Meetings, and Learning Videos. 2) students enter school with alternating schedules according to the schedule during the pandemic. The conclusion in this study is that the teacher's learning implementation strategy has been carried out offline and online using a variety of technological media that can be used to achieve learning objectives in accordance with the applicable curriculum.